2007
DOI: 10.1111/j.1365-2249.2007.03491.x
|View full text |Cite
|
Sign up to set email alerts
|

Leptin improves pulmonary bacterial clearance and survival inob/obmice during pneumococcal pneumonia

Abstract: SummaryThe adipocyte-derived hormone leptin is an important regulator of appetite and energy expenditure and is now appreciated for its ability to control innate and adaptive immune responses. We have reported previously that the leptindeficient ob/ob mouse exhibited increased susceptibility to the Gram-negative bacterium Klebsiella pneumoniae. In this report we assessed the impact of chronic leptin deficiency, using ob/ob mice, on pneumococcal pneumonia and examined whether restoring circulating leptin to phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
126
1
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(136 citation statements)
references
References 43 publications
5
126
1
4
Order By: Relevance
“…In humans, leptin has also been shown to be a predictor of lung function and lung volume [27]. In contrast to our study serum leptin concentrations are often reported to be increased in inflammatory and infectious conditions [28,29].…”
Section: Discussioncontrasting
confidence: 95%
“…In humans, leptin has also been shown to be a predictor of lung function and lung volume [27]. In contrast to our study serum leptin concentrations are often reported to be increased in inflammatory and infectious conditions [28,29].…”
Section: Discussioncontrasting
confidence: 95%
“…The role of leptin in the response to sepsis and pulmonary infections remains a subject of debate. Mouse models of leptin deficiency (ob/ob mice) have exhibited reduced bacterial clearance and increased mortality, shown to be related to impaired alveolar macrophage phagocytosis, reduced lung neutrophil counts and levels of pro-inflammatory cytokines [30,31]. Exogenous administration of leptin improved survival and pulmonary bacterial clearance and reduced bacteraemia in ob/ob mice [31].…”
Section: Discussionmentioning
confidence: 99%
“…A protective role of leptin in the clearance from pathogens is observed in leptin-deficient ob/ ob mice, which develop severe disease and die of infection with Klebsiella more rapidly than wild-type mice [102][103]. The ob/ob mice are also highly susceptible to LPS-induced lethality, which can be reversed by the administration of leptin [104][105].…”
Section: Leptin and Acute Inflammationmentioning
confidence: 99%